2022
DOI: 10.3389/fneur.2022.1012668
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of autonomic symptom burden in long COVID: A global survey of 2,314 adults

Abstract: BackgroundAutonomic dysfunction is a known complication of post-acute sequelae of SARS-CoV-2 (PASC)/long COVID, however prevalence and severity are unknown.ObjectiveTo assess the frequency, severity, and risk factors of autonomic dysfunction in PASC, and to determine whether severity of acute SARS-CoV-2 infection is associated with severity of autonomic dysfunction.DesignCross-sectional online survey of adults with PASC recruited through long COVID support groups between October 2020 and August 2021.Participan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
0
37
0
4
Order By: Relevance
“…POTS is associated with G protein-coupled adrenergic receptor and muscarinic acetylcholine receptor autoantibodies, platelet storage pool deficiency, small fibre neuropathy and other neuropathologies 118 . Both POTS and small fibre neuropathy are commonly found in long COVID 111 , 119 , with one study finding POTS in 67% of a cohort with long COVID 120 .…”
Section: Major Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…POTS is associated with G protein-coupled adrenergic receptor and muscarinic acetylcholine receptor autoantibodies, platelet storage pool deficiency, small fibre neuropathy and other neuropathologies 118 . Both POTS and small fibre neuropathy are commonly found in long COVID 111 , 119 , with one study finding POTS in 67% of a cohort with long COVID 120 .…”
Section: Major Findingsmentioning
confidence: 99%
“…1 ). Long COVID encompasses multiple adverse outcomes, with common new-onset conditions including cardiovascular, thrombotic and cerebrovascular disease 8 , type 2 diabetes 9 , myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) 10 , 11 and dysautonomia, especially postural orthostatic tachycardia syndrome (POTS) 12 (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies cause peripheral vasoconstriction to be less effective and eventually cause reflex tachycardia. It has been observed that many patients with COVID-19 infection develop POTS as a delayed manifestation [9][10][11]19,22]. Some of these patients have never experienced any symptoms of POTS before.…”
Section: Normal Orthostatic Responsementioning
confidence: 99%
“…Its pathophysiology is postulated to include virus-or immune-mediated damage to the autonomic nervous system. Autonomic dysfunction, of which POTS is an important subset, has been noted in more than half the patients with COVID-19 as post-acute sequelae in some studies [19]. Understanding these critical sequelae of COVID-19 for early diagnosis and effective management is essential.…”
Section: Introductionmentioning
confidence: 99%
“… 95 In a survey of 2413 adults between 18 and 64 years of age with PASC after confirmed positive testing for SARS-CoV-2, 66% had a Composite Autonomic Symptom Score-31 >20 suggesting moderate-severe autonomic dysfunction independent of the severity of acute infection and requirement of hospitalization. 96 …”
Section: Pathogenic Theories In Pascmentioning
confidence: 99%